Al-Ansyhiṭah al-Lugawiyyah fī Ḍaui al-Ma’āyir al-Khamsah ACTFL ladā al-Thalabah bi Ma‘had Darrullughah Wadda‘wah wa Ma‘had Sidogiri: Language Activities in the Perspective of Five ACTFL Standards for Students in Ma'had Darrullughah Wadda'wah wa Ma'had Sidogiri - Syamfa Agny Anggara; Alvia Putri Prima Sari; Mustahar Ali Wardana (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2024)
Language activities have a significant role in shaping student language skills. Students' language competence is the standard for success in language activities in Islamic boarding schools. The objectives of this study include interpreting language activities inside and outside the classroom in Darullugah Wadda'wah (DALWA) and Sidogiri Islamic Boarding School. The researcher used a qualitative approach with a multi-case study method. The collected data includes primary data and secondary data. Data collection techniques include observation, interviews, and documentation. The data analysis technique used the Miles and Huberman model, starting from collecting data and analyzing, selecting, presenting, and concluding. The results of this study indicate that the language activities in DALWA include activities inside and outside the classroom. Activities in the classroom include morning and evening halaqah, speeches, dramas, memorization, and Arabic announcements. Meanwhile, activities outside the classroom include speeches, dramas, memorization, Arabic announcements, and wall magazines. All DALWA activities aim to create a language environment in the Islamic Boarding School. The language activities in Sidogiri include activities inside and outside the classroom. Activities in the classroom include halaqah, additional classes, discussion of language areas, and memorizing mufrodat. Meanwhile, activities outside the classroom include speeches, dramas, memorization, Arabic announcements, and wall magazines. All activities in Sidogiri aim to create a language environment in the Language Area. Language activities in DALWA and Sidogiri have standard language readiness, including communication, cultures, connections, comparisons, and communities. Keywords: ACTFL, Language Activities, Readiness Language   ملخص للأنشطة اللغوية لها دور مهم في تشكيل  المهارات اللغوية لدى الطلاب. كفاءات اللغوية الطلاب معيار  النجاح لأنشطة الغوية  في المعهد الإسلامي. يستهدف هذا البحث إلى شرح الأنشطة اللغوية داخل وخارج الفصل بمعهد دار اللغة والدعوة ومعهد سيدوجيري.  يُستخدم هذا البحث دراسة الحالة المتعددة. وتحتوي البييانات المحصولة  من  المصادر الأولى والثانوية. جمع البيانات بالملاحظة والمقابلة والوثائق. وأما تحليل البيانات عند مايلز وهوبرمان، وتبدأ من جمع البيانات والاختيار والعرض والاستنتاج. تشير نتائج هذه الدراسة إلى أن  الأنشطة اللغوية في دار اللغة والدعوة تتضمن على أنشطة داخل الفصل وخارجه. وأنشطة داخل الفصل هي   حلقات صباحية ومسائية والخطابة والمسرحية والحفظ والإعلانات العربية ، وخارج الفصل  الخطابة والمسرحية والحفظ والمجلات الحائطية. تهدف جميع أنشطة دار اللغة والدعوة إلى تكوين البيئة اللغوية في المعهد.  وكذلك لأنشطة اللغوية في سيدوجيري داخل الفصل هي الحلقة والفصول الإضافية ومناقشة اللغة  وحفظ لمفردات،  وخارج الفصل الخطابة والمسرحية والحفط والإعلانات العربية والمجلات الحائطية . وتهدف الأنشطة في سيدوجيري إلى تكوين البيئة. والأنشطة في دار اللغة والدعوة وسيدوجيري لها الاستعداد اللغوي، بما فيه الاتصال والثقافة والروابط والمقارنة والمجتمع الكلمات المفتاحية:  ACTFL، الأنشطة اللغوية، الاستعداد اللغوي